2005
DOI: 10.1007/s00402-005-0802-x
|View full text |Cite
|
Sign up to set email alerts
|

Intraspinal metalloma resulting in late paraparesis

Abstract: The metal-related complications caused by orthopedic implants have long been a concern, but these problems have been considered mostly in the field of arthroplasty or internal fixation of fractures. The recent prevalence of spinal instrumentation has evoked a similar concern among spine surgeons. Here, we present a case of intraspinal metallosis adjacent to the pedicular hook occurring after treatment of vertebral fracture by posterior spinal instrumentation and fusion, and causing paraparesis at the 3rd posto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 32 publications
0
33
1
1
Order By: Relevance
“…2 A metal in living tissue is prone to corrosion due to electrochemical reactions. 4 In addition to the wellinvestigated electrochemical aspect of corrosion in a physiological system, this study demonstrates that human OC grow as well on SS as they grow on glass, and are able to directly corrode the metal surface and subsequently release metal ions. Furthermore, these results indicate that the released metal ions may cause inflammatory reactions by inducing the secretion of proinflammatory cytokines IL-1b, IL-6, and TNF-a, which in Figure 3.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…2 A metal in living tissue is prone to corrosion due to electrochemical reactions. 4 In addition to the wellinvestigated electrochemical aspect of corrosion in a physiological system, this study demonstrates that human OC grow as well on SS as they grow on glass, and are able to directly corrode the metal surface and subsequently release metal ions. Furthermore, these results indicate that the released metal ions may cause inflammatory reactions by inducing the secretion of proinflammatory cytokines IL-1b, IL-6, and TNF-a, which in Figure 3.…”
Section: Discussionmentioning
confidence: 70%
“…1 However, their permanent tendency to corrode when exposed to a physiological environment remains a serious concern. [2][3][4] Elevated concentrations of metal ions have been measured in clinically retrieved peri-prosthetic tissues, distal organs, and body fluids in total hip arthroplasty patients. [5][6][7] The biology behind corrosion inside the human body and the distribution of the metal ions throughout the organism is not fully understood.…”
mentioning
confidence: 99%
“…But with other types of implants this is not observed. Looking at the cases reported by Tezer [26] and Takahashi [25], with neurological symptoms in relation to corrosion, no radiological signs of corrosion are seen in plain radiographies. It is possible that for other kinds of instrumentations, like CD or TSRH, in which corrosion has been reported in the literature, metal levels can be more useful than looking for radiographic signs of corrosion.…”
Section: Discussionmentioning
confidence: 90%
“…Also, specific localization of the corrosion site may determine other complications. In spinal implants, Tezer et al [26] and Takahashi et al [25] have reported delayed neurological symptoms caused by intraspinal metallosis, including radiculopathy and paraparesis.…”
Section: Introductionmentioning
confidence: 99%
“…The first intraspinal metallosis causing delayed neurologic symptoms after spinal instrumentation was reported by Takahashi et al [6]. Intraspinal metalloma resulting in late paraparesis was also reported by Tezer et al [7]. A case of intraspinal metallosis adjacent to the pedicular hook, which developed after thoracic vertebral fracture treatment, caused paraparesis at the 3rd postoperative year.…”
Section: Discussionmentioning
confidence: 89%